2018
DOI: 10.1177/0260106018777170
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between vitamin A intake, serum vitamin A, and risk of liver cancer

Abstract: Current information on the association between vitamin A intake and liver cancer or serum vitamin A and liver cancer are limited. Most studies demonstrated no association between dietary vitamin A and the risk of liver cancer. However, the finding was based on a small number of studies with potential publication bias. Therefore, large observational studies should be conducted to confirm these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The unique phenomenon of pale leaves and lethal phenotype of the plants, which caused by inhibiting the desaturation process, have been usually used to evaluate the efficiency of genetic modification technology (Kaur et al, 2018). Meanwhile, carotenoids are also used as nutrient supplements (Leelakanok et al, 2018) and chemotherapy reagents (Noto et al, 1996). Genes involved in the carotenoid biosynthesis have been isolated and identified for enzymatic activities analysis (Norris et al, 1995;Liu et al, 2013;Brausemann et al, 2017), nutritional enhancements of food (Wurtzel et al, 2003) and genetical modification technology tools (Velasquez et al, 2009;Kaur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The unique phenomenon of pale leaves and lethal phenotype of the plants, which caused by inhibiting the desaturation process, have been usually used to evaluate the efficiency of genetic modification technology (Kaur et al, 2018). Meanwhile, carotenoids are also used as nutrient supplements (Leelakanok et al, 2018) and chemotherapy reagents (Noto et al, 1996). Genes involved in the carotenoid biosynthesis have been isolated and identified for enzymatic activities analysis (Norris et al, 1995;Liu et al, 2013;Brausemann et al, 2017), nutritional enhancements of food (Wurtzel et al, 2003) and genetical modification technology tools (Velasquez et al, 2009;Kaur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental animal studies, long‐term administration of bromelain has exhibited an antihypertensive effect, indicating that bromelain supplements may reduce risk factors associated with cardiovascular diseases [33] . It is important to note that one of the main reasons for bromelain‘s anticancer property is its ability to inhibit blood platelet aggregation, which plays a crucial role in blood clotting [34] . Bromelain has been found to exhibit fibrinolytic activity, inhibit thrombus formation, and reduce platelet aggregation, thus impeding blood clotting [33] .…”
Section: Pharmacological Properties and Health Benefits Of Pineapple ...mentioning
confidence: 99%
“…One systematic review and meta-analysis including 10 studies showed that vitamin A intakes were not associated with all-cause mortality among pre-diagnostic or post-diagnostic breast cancer patients ( 11 ). Another systematic review and meta-analysis of five studies found an inconclusive association between serum retinol and liver cancer ( 12 ). In a systematic review and meta-analysis of 11 studies on the risk association between vitamin A intake and cervical cancer, dietary total vitamin A intake and its components (retinol, β-carotene, and other carotenoids) were all inversely associated with cervical cancer ( 13 ).…”
Section: Health Outcomes Relevant For Nordic and Baltic Countriesmentioning
confidence: 99%